Los elementos onomásticos ibéricos -kibaś y -tibaś (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This article deals with Iberian onomastic elements -kibaś and -tibaś. To start from considering baś as an equivalent to ‘gift’ we propose the isolation of other two elements ti- and -ki. Ti- would be a verbalizer and perfective element similar in its function to the Greek word -dotós whereas -ki would be a pluralizer element wich in fact of the compound belongs to the first member.
Keywords: Iberian Onomastics; Iberian Language; Iberian Epigraphy